Novel KCNQ1 Q234K variant, identified in patients with long QT syndrome and epileptiform activity, induces both gain- and loss-of-function of slowly activating delayed rectifier potassium currents - Nakajima, Tadashi; Tamura, Shuntaro; Kawabata-Iwakawa, Reika; Itoh, Hideki; Hasegawa, Hiroshi; Kobari, Takashi; Harasawa, Shun; Sekine, Akiko; Nishiyama, Masahiko; Kurabayashi, Masahiko; Imoto, Keiji; Kaneko, Yoshiaki; et al. (Frontiers in Physiology, 2024)
Introduction: KCNQ1 and KCNE1 form slowly activating delayed rectifier potassium currents (IKs).Loss-of-function of IKs by KCNQ1 variants causes type-1 long QT syndrome (LQTS). Also, some KCNQ1 variants are reported to cause epilepsy. Segment 4 (S4) of voltage-gated potassium channels has several positively-charged amino acids that are periodically aligned, and acts as a voltage-sensor.Intriguingly, KCNQ1 has a neutral-charge glutamine at the third position (Q3) in the S4 (Q234 position in KCNQ1), which suggests that the Q3 (Q234) may play an important role in the gating properties of IKs. We identified a novel KCNQ1 Q234K (substituted for a positively-charged lysine) variant in patients (a girl and her mother) with LQTS and epileptiform activity on electroencephalogram. The mother had been diagnosed with epilepsy. Therefore, we sought to elucidate the effects of the KCNQ1 Q234K on gating properties of IKs.Methods: Wild-type (WT)-KCNQ1 and/or Q234K-KCNQ1 were transiently expressed in tsA201cells with KCNE1 (E1) (WT+E1-channels, Q234K+E1-channels, and WT+Q234K+E1-channels), and membrane currents were recorded using whole-cell patch-clamp techniques.Results: At 8-s depolarization, current density (CD) of the Q234K+E1-channels or WT+Q234K+E1channels was significantly larger than the WT+E1-channels (WT+E1: 701±59 pA/pF; Q234K+E1: 912±50 pA/pF, P<0.01; WT+Q234K+E1: 867±48 pA/pF, P<0.05). Voltage dependence of activation (VDA) of the Q234K+E1-channels or WT+Q234K+E1-channels was slightly but significantly shifted to depolarizing potentials in comparison to the WT+E1-channels ([V1/2] WT+E1: 25.6±2.6 mV; Q234K+E1: 31.8±1.7 mV, P<0.05; WT+Q234K+E1: 32.3±1.9 mV, P<0.05). Activation rate of the Q234K+E1-channels or WT+Q234K+E1-channels was significantly delayed in comparison to the WT+E1 channels ([half activation time] WT+E1: 664±37 ms; Q234K+E1: 1417±60 ms, P<0.01; WT+Q234K+E1: 1177±71 ms, P<0.01). At 400-ms depolarization, CD of the Q234K+E1-channels or WT+Q234K+E1-channels was significantly decreased in comparison to the WT+E1-channels (WT+E1: 392±42 pA/pF; Q234K+E1: 143±12 pA/pF, P<0.01; WT+Q234K+E1: 209±24 pA/pF, P<0.01) due to delayed activation rate and depolarizing shift of VDA.The KCNQ1 Q234K induced IKs gain-of-function during long (8-s)-depolarization, while loss of-function during short (400-ms)-depolarization, which indicates that the variant causes LQTS, and raises a possibility that the variant may also cause epilepsy. Our data provide novel insights into the functional consequences of charge addition on the Q3 in the S4 of KCNQ1.